Measuring the Broader Value Proposition of Digital Transformation in Supply Chains - Singh, Pratyush Kumar Kumar (International Journal of Supply Chain Management, 2024)
The advent of digital transformation within supply chains heralds a new era of efficiency, innovation, and resilience. This paper explores the multifaceted impact of digital technologies—such as the Internet of Things (IoT), artificial intelligence (AI), blockchain, and cloud computing—on supply chain management. Through a comprehensive review of current literature, we identify the challenges and opportunities presented by digital transformation, emphasizing the importance of overcoming infrastructural constraints, skill gaps, and security concerns to harness the full potential of these technologies. Furthermore, we delve into the ethical considerations and social impacts, highlighting the imperative for sustainable and responsible practices in the digital age. The paper also forecasts future directions and emerging technologies, underscoring the need for supply chains to adapt to and capitalize on these advancements for sustainable growth and competitive advantage. Our analysis concludes that while digital transformation presents significant challenges, it also offers unparalleled opportunities for supply chains to become more agile, transparent, and customer centric. The successful integration of digital technologies not only enhances operational efficiency but also drives innovation, fosters sustainability, and strengthens resilience against global disruptions. This paper contributes to the ongoing discourse on digital transformation in supply chains, providing insights for academics, practitioners, and policymakers on navigating the complexities of this digital revolution.